Familia y culturas juveniles - Guerrero De la Cruz, María Daniela; Quevedo Pinta, Jorge Ariel (Machala : Universidad Técnica de Machala, 2019)
The research work responds to the need to comply with the requirement of a degree corresponding to the degree in Sociology and Political Sciences, which is registered in the option of graduation of Degree Work, under the Integrated Project modality, of the Technical University of Machala UTMACH, the same that will be based on the study of the Socio-familiar Impact of Youth Cultural Manifestations in the City of El Guabo, El Oro Province, in 2019. Culture is a fundamental pillar in the development of society and of the individuals that make it up, since all the characteristics of society are present in it, culture is transmitted from generation to generation; it is worth noting that in the canton of El Guabo, it has not been a priority of the authorities in power or the institutions present to conserve and cultivate the indigenous cultural features of the sector, seeing in the new family generations a great detachment from territorial traditions. Since there is cultural disinterest from the family nucleus, young people do not have a defined orientation, becoming subjects in search of an identity and acculturation. Society is facing major transformations that have taken on a growing collective interest in the social and cultural sphere; as far as youth cultures are concerned, adolescents are the most involved in this context, as they seek identity and independence through it.
El trabajo de investigación obedece a la necesidad de cumplir con el requerimiento de titulación correspondiente a la carrera de Sociología y Ciencias Políticas, que se inscribe en la opción de graduación de Trabajo de Titulación, bajo la modalidad Proyecto Integrador, de la Universidad Técnica de Machala UTMACH, el mismo que se basará en el estudio del Impacto Socio-familiar de las Manifestaciones Culturales Juveniles en la Ciudad de El Guabo, Provincia de El Oro, en el año 2019. La cultura es un pilar fundamental en el desarrollo de la sociedad y de los individuos que la conforman, ya que en ella están presente todas las características de la sociedad; la cultura es trasmitida de generación en generación, cabe destacar que en el cantón El Guabo, no ha sido prioridad de las autoridades de turno o de las instituciones presentes el conservar y cultivar los rasgos culturales autóctonos del sector, viendo en las nuevas generaciones familiares gran desapego a las tradiciones territoriales. Al existir desinterés cultural desde el núcleo familiar, los jóvenes no tienen una orientación definida, convirtiéndose en sujetos en búsqueda de una identidad y al aculturamiento. La sociedad se enfrenta a grandes trasformaciones que han cobrado un creciente interés colectivo en el ámbito social y cultural, en cuanto refiere a las culturas juveniles, los adolescentes son los más implicados en este contexto, ya que buscan a través de ella identidad e independencia.
Keywords: CULTURA; URBANA; JUVENIL; RESISTENCIA SOCIAL